Letter to the editor: The small (14 Fr) percutaneous catheter (P-CAT) versus large (28–32 Fr) open chest tube for traumatic hemothorax: A multicenter randomized clinical trial. Issue 3 (25th September 2022) - Hylands, Mathieu; Gomez, David; Beckett, Andrew
Abstract : Pigtail catheters may be preferable to large-bore chest tubes in stable patients with traumatic hemothorax. However, we argue the recent randomized controlled trial comparing the two has not established either the safety or efficacy of small-bore pigtail catheters in trauma.